Self-assembly of flagellin on Au (111) surfaces - González Orive, Alejandro (2014)
The adsorption of flagellin monomers from Pseudomonas fluorescens on Au(111) has been studied by Atomic Force Microscopy (AFM), Scanning Tunneling Microscopy (STM), X-ray Photoelectron Spectroscopy (XPS), Surface Plasmon Resonance (SPR), and electrochemical techniques. Results show that flagellin monomers spontaneously self-assemble forming a monolayer thick protein film bound to the Au surface by the more hydrophobic subunit and exposed to the environment the hydrophilic subunit. The films are conductive and allow allocation of electrochemically active cytochrome C. The self-assembled films could be used as biological platforms to build 3D complex molecular structures on planar metal surfaces and to functionalize metal nanoparticles